Application of hydraulic device as working bodies of the road-building machines - I. A. Semenova (Вестник СибАДИ, 2017)
This article presents the results of work on the definition of the basic design features and energy hydropercussion devices used as the working bodies of road-building machinery. The main factors affecting the process of destruction of the soil (hard material) of hydraulic device. A promising design of hydraulic device (breaker), with several working bodies, as well as shows the basic hydraulic circuit using multiple hammers.